Finding harmony so the music plays on: pragmatic trial design considerations to promote organizational sustainment of an empirically-supported behavior therapy. Issue 1 (December 2016) - Hartzler, Bryan; Peavy, K.; Jackson, T.; Carney, Molly
Abstract Background Pragmatic trials of empirically-supported behavior therapies may inform clinical and policy decisions concerning therapy sustainment. This retrospective trial design paper describes and discusses pragmatic features of a hybrid type III implementation/effectiveness trial of a contingency management (CM) intervention at an opioid treatment program. Prior reporting (Hartzler et al., J Subst Abuse Treat 46:429–438, 2014; Hartzler, Subst Abuse Treat Prev Policy 10:30, 2015) notes success in recruiting program staff for voluntary participation, durable impacts of CM training on staff-level outcomes, provisional setting implementation of the intervention, documentation of clinical effectiveness, and post-trial sustainment of CM. Methods/design Six pragmatic design features, and both scientific and practical bases for their inclusion in the trial, are presented: (1) a collaborative intervention design process, (2) voluntary recruitment of program staff for therapy training and implementation, (3) serial training outcome assessments, with quasi-experimental staff randomization to either single or multiple baseline assessment conditions, (4) designation of a 90-day period immediately after training in which the setting implemented the intervention on a provisional basis, (5) inclusive patient eligibility for receipt of the CM intervention, and (6) designation of two staff as local implementation leaders to oversee clinical/administrative issues in provisional implementation. Discussion Each pragmatic trial design feature is argued to have contributed to sustainment of CM. Contributions implicate the building of setting proprietorship for the CM intervention, culling of internal staff expertise in its delivery, iterative use of assessment methods that limited setting burden, documentation of setting-specific clinical effectiveness, expanded penetration of CM among staff during provisional implementation, and promotion of setting self-reliance in the oversight of sustainable implementation procedures. It is hoped this discussion offers ideas for how to impact local clinical and policy decisions via effective behavior therapy dissemination.